The Role of Immune Modulation in Pathogenesis of IgA Nephropathy - Chang, Sheng; Li, Xiao-Kang (Frontiers in Medicine, 2020)
IgA nephropathy (IgAN) is the most prevalent primary glomerulonephritis worldwide, with diverse clinical manifestations characterized by recurrent gross hematuria or microscopic hematuria, and pathological changes featuring poorly O-galactosylated IgA1 deposition in the glomerular mesangium. Pathogenesis has always been the focus of IgAN studies. After 50 years of research, most scholars agree that IgAN is a group of clinicopathological syndromes with certain common immunopathological characteristics, and multiple mechanisms are involved in its pathogenesis, including immunology, genetics, and environmental or nutritional factors. However, the precise pathogenetic mechanisms have not been fully determined. One hypothesis about the pathogenesis of IgAN suggests that immunological factors are engaged in all aspects of IgAN development and play a critical role. A variety of immune cells (e.g., dendritic cells, NK cells, macrophages, T-lymphocyte subsets, and B-lymphocytes, etc.) and molecules (e.g., IgA receptors, Toll-like receptors, complements, etc.) in innate and adaptive immunity are involved in the pathogenesis of IgAN. Moreover, the abnormality of mucosal immune regulation is the core of IgAN immunopathogenesis. The roles of tonsil immunity or intestinal mucosal immunity, which have received more attention in recent years, are supported by mounting evidence. In this review, we will explore the latest research insights on the role of immune modulation in the pathogenesis of IgAN. With a better understanding of immunopathogenesis of IgAN, emerging therapies will soon become realized.